Pengakuan Pendapatan dan Biaya dalam Kaitannya dengan Penentuan Laba Perusahaan Ekspedisi (Studi Kasus pada PT. EMKL Jelutung Subur) - Yuli Anwar (STIE Binaniaga, 2010)
Revenue and cost recognitions is the most important thing to be done by an entity, time and the recognition method must be based on the rules from Financial Accounting Standards. Revenue and cost recognition which is done by PT. EMKL Jelutung Subur located on Pangkalpinang, Bangka Belitung province is done by using the accrual basis, and it can be seen with its influences to company profits every year. This research is useful to get a data and information for preparing this thesis and improving my knowledge and also for comparing between theories accepted against facts applied in the field. The result of this research shows that PT. EMKL Jelutung Subur has implemented one of the revenue and cost recognition method (accrual basis) continually, so that profit accuracy is accountable to be used for developing this kind of expedition business in order to become a better company. The accuracy is evaluated because all revenues received and cost spent have clear evidence and found in the period of time. The evaluation shows there is one thing that miss from revenue and cost recognition done by PT. EMKL Jelutung Subur, that is charge to the customers who use the storage service temporary, because some customers keep their goods for a long time in the warehouse, and it will increase the costs of loading, warehouse maintenance, damaged goods and decreasing a quantity of goods. If the storage service is charged to the customers, PT. EMKL Jelutung Subur will earn additional revenue to cover all the expenses above